2020
DOI: 10.7322/jhgd.v30.10365
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of violence among students of public schools

Abstract: Introduction: School violence it’s a problem that involves a lot of bad consequences for the life’s students. So preventing and research about it are very important. Objective: The objective of this study was identify the experiences of violence of students from public schools participating in the PSE - School Health Program and SPE - Health and Prevention in the Schools of Florianópolis. Methods: Participants were 871 students from the 9th grade of elementary school to the 3rd year of high school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Also In South America, a study of Brazilian adolescents reported that domestic violence against adolescents is related to family interactions, the use of psychoactive substances and violence in the school environment (28). Another research in Brazil conducted in 871 students attending public schools, reported that 15.3% had already consumed some type of drug, 13.2% claimed to have already consumed marijuana, 3.3% cocaine and 0.1% crack; 65.3% claimed to have drunk alcohol abusively in a short space of time (67.4% boys and 63.3% girls) (29). In Colombia in 2015, a sample of 500 adolescents from 20 public educational institutions was studied, nding verbal violence (66.5%) followed by physical (32.0%) and exclusion (30.6%); an association was also found between being a victim and presenting some disability, verbal aggression at home and drug use (30).…”
Section: Discussionmentioning
confidence: 99%
“…Also In South America, a study of Brazilian adolescents reported that domestic violence against adolescents is related to family interactions, the use of psychoactive substances and violence in the school environment (28). Another research in Brazil conducted in 871 students attending public schools, reported that 15.3% had already consumed some type of drug, 13.2% claimed to have already consumed marijuana, 3.3% cocaine and 0.1% crack; 65.3% claimed to have drunk alcohol abusively in a short space of time (67.4% boys and 63.3% girls) (29). In Colombia in 2015, a sample of 500 adolescents from 20 public educational institutions was studied, nding verbal violence (66.5%) followed by physical (32.0%) and exclusion (30.6%); an association was also found between being a victim and presenting some disability, verbal aggression at home and drug use (30).…”
Section: Discussionmentioning
confidence: 99%
“…Within this aspect, which is related to a stage of childhood development, it presents a study on new screening instruments for child development in Brazil, considering those used in different studies 19 . At another point, an interesting study that discusses other forms of violence experienced by students in public schools, considering risky, leisure, violent behaviors and other variables 20 .…”
mentioning
confidence: 99%